Knowledge regarding preventive measures of pressure ulcer among nurses - Neupane, Gita; Sah, Chanda (Journal of Chitwan Medical College, 2020)
Background: Pressure ulcer is a preventable medical complication. Nurses are primarily responsible in pressure ulcer prevention. This study was designed to find out knowledge regarding preventive measures of pressure ulcer among nurses. Methods: Descriptive study was conducted among 100 nurses, selected by using non-probability convenience sampling technique. Pretested Self-administered semi-structured questionnaire was used and collected data were analyzed by using descriptive and inferential statistics with Statistical Package for Social Sciences software version 20.0. Results: The findings of the study revealed that nearly half (48%) of the respondents had low knowledge regarding pressure ulcer. Regarding age, majority (52%) of the respondents were of age group 18-27 years. Regarding qualification, 48% of the respondents were PCL nursing and 47% had working experience of 1-5 years. Similarly, 17% of respondents were working in Gynecology ward and 85% had exposed to managed patients with pressure ulcer. Among them, 76% of the respondents had knowledge regarding meaning and 96% had knowledge regarding signs of pressure ulcer. Ninety two percent of the respondents had knowledge that position of patients should be changed every 2 hourly, 38% had knowledge that patient’s head should be elevated at or below 300 and 73% had knowledge that normal saline is the best solution to cleanse pressure ulcer. There was statistically significant association of respondents’ level of knowledge regarding ulcer with working department (p=0.001). Conclusions: The study concluded that nearly half of the nurses have low knowledge regarding pressure ulcer. It is recommended to hospital management to conduct in-service education for nurses.